2022
DOI: 10.21873/cgp.20352
|View full text |Cite
|
Sign up to set email alerts
|

TMED9Expression Level as a Biomarker of Epithelial Ovarian Cancer Progression and Prognosis

Abstract: Background: Transmembrane emp24 domaincontaining protein 9 (TMED9) belongs to the TMED/p24 family that transports, modifies, and packs proteins and lipids into vesicles for delivery to specific locations and is important in innate immune signaling via the endoplasmic reticulum-Golgi cargo pathway. TMED9 has been implicated in various cancer types; however, its role in epithelial ovarian cancer (EOC) is unclear. In this study, we aimed to elucidate the role and clinical significance of TMED9 in EOC. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A recent study confirmed that high TMED9 expression was correlated to progression, plasma cell type, and inferior histological grade in epithelial ovarian cancer, which demonstrates potential predictive value for both disease-free and overall survival. More in-depth functional studies revealed that TMED9 knockdown decreased epithelial ovarian carcinoma (EOC) cells' migration, invasion, cell proliferation, and colony formation, indicating TMED9 might be a useful prognostic biomarker and supporting the idea that targeting TMED9 might be an innovative approach to treating EOC 61 .…”
Section: Progress Of the Tmed Family In Some Common Human Diseasesmentioning
confidence: 91%
“…A recent study confirmed that high TMED9 expression was correlated to progression, plasma cell type, and inferior histological grade in epithelial ovarian cancer, which demonstrates potential predictive value for both disease-free and overall survival. More in-depth functional studies revealed that TMED9 knockdown decreased epithelial ovarian carcinoma (EOC) cells' migration, invasion, cell proliferation, and colony formation, indicating TMED9 might be a useful prognostic biomarker and supporting the idea that targeting TMED9 might be an innovative approach to treating EOC 61 .…”
Section: Progress Of the Tmed Family In Some Common Human Diseasesmentioning
confidence: 91%
“…Similarly, elevated TMED9 expression is associated with reduced survival time in individuals with epithelial ovarian cancer (EOC) in vivo. TMED9 knockdown reduces EOC cell proliferation in vitro ( Han et al, 2022 ).…”
Section: Tmed9 Interactions In Health and Diseasementioning
confidence: 99%
“…4A and B, the expressions of 9764 genes were positively correlated with the expression of hnRNPAB, and 10214 genes were negatively correlated with hnRNPAB. Several hnRNPAB-positive correlated genes with high Pearson Correlations that have been reported to be associated with tumorigenesis were screened to perform the co-expression analysis with hnRNPAB using the mRNA expression data of 585 LUAD and 550 LUSC samples obtained from the TCGA database, including NOP16 nucleolar protein (NOP16), nucleophosmin 1 (NPM1), treacle ribosome biogenesis factor 1 (TCOF1), centromere protein H (CENPH), cyclin B1 (CCNB1), heat shock protein family A (Hsp70) member 9 (HSPA9), sideroflexin 1 (SFXN1), protein phosphatase, Mg 2+ /Mn 2+ dependent 1G (PPM1G), transmembrane p24 trafficking protein 9 (TMED9), and DEAD-box helicase 41 (DDX41) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). As shown in Fig.…”
Section: Analysis Of Genes Related To Hnrnpab Expression In Nsclcmentioning
confidence: 99%